2015
DOI: 10.3109/14017431.2015.1023343
|View full text |Cite
|
Sign up to set email alerts
|

Phase analysis detects heterogeneity of myocardial deformation on cine MRI

Abstract: This is the pre peer-reviewed version of the following article, "Phase analysis detects heterogeneity of myocardial deformation on cine MRI", which in its final form has been published at Scand Cardiovasc J. This is the pre peer-reviewed version of the following article, "Phase analysis detects heterogeneity of myocardial deformation on cine MRI", which in its final form has been published at Scand Cardiovasc J. This is the pre peer-reviewed version of the following article, "Phase analysis detects heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Strain analysis, which can express deformation of a tissue or organ in the human body, has been mainly used to assess myocardial motion using various four-dimensional (4D) imaging modalities, including echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT) 111. Although various parameters based on strain measurements have been advocated by different software vendors, it is commonly accepted in the field of cardiology that strain is a sensitive parameter to assess regional function of the myocardium 411.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strain analysis, which can express deformation of a tissue or organ in the human body, has been mainly used to assess myocardial motion using various four-dimensional (4D) imaging modalities, including echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT) 111. Although various parameters based on strain measurements have been advocated by different software vendors, it is commonly accepted in the field of cardiology that strain is a sensitive parameter to assess regional function of the myocardium 411.…”
Section: Introductionmentioning
confidence: 99%
“…Strain analysis, which can express deformation of a tissue or organ in the human body, has been mainly used to assess myocardial motion using various four-dimensional (4D) imaging modalities, including echocardiography, magnetic resonance imaging (MRI), and computed tomography (CT) 111. Although various parameters based on strain measurements have been advocated by different software vendors, it is commonly accepted in the field of cardiology that strain is a sensitive parameter to assess regional function of the myocardium 411. It has also been reported that strain measurements reveal minor left ventricular modifications in athletes with common anomalies (ie, bicuspid aortic valve),3 which might be masked by apparently normal values of global cardiac function parameters, such as ejection fraction and stroke volume 12,13…”
Section: Introductionmentioning
confidence: 99%